Окремі питання допустимості доказів у цивільному процесі України - Теремецький, В. І.; Teremetskyi, V. I. (Науковий вісник Академії муніципального управління. Серія : Право. - 2015. - Вип. 1, ч. 2. - С. 128-135, 2015)
Досліджено проблематику допустимості доказів у сучасному цивільному процесі з урахуванням оновленої об’єктивної форми існування доказів та новітніх технологій дослідження фактичних обставин у цивільній справі. Розглянуто наукові дискусії щодо категорії «докази» та правові позиції, які сформувались стосовно допустимості доказів.

The development of social relations, scientific and technical process leads to the establishment of new objective forms of existence of evidence. Thus, with the emergence of electronic documents, electronic signatures, IP - addresses, other updates there was a necessity to research these phenomena as evidence in civil proceedings. Herewith, determining the admissibility of evidence is an important issue as the court takes into account only the evidence which meet the criteria of admissibility The article’s objective is determining the concept and features of establishing the admissibility of evidence in the civil proceedings of Ukraine. The author of the article considers the problems of admissibility of evidence in the modern civil procedure taking into account the revised objective form of existence of evidence and new technologies of researching factual circumstances in a civil case. Scientific debates concerning the category of “evidence” and legal positions that were formed in regard to the admissibility of evidence are considered. It is concluded that electronic evidence – are the evidence that have digital objective form, obtained in the manner prescribed by the law and contain information about the facts, on the basis of which the court determines the presence or absence of circumstances of a case. They include: electronic document, electronic databases, audio and video materials, E-mail correspondence, electronic signature. The features of electronic evidence are characterized. It is established that the admissibility – is a property of evidence, which characterizes it in terms of procedural form: legality of a source of obtaining information, the ways of getting the evidence by an authorized subject as a result of conducted proceedings while keeping the law, aiming to establish the truth in a case. Admissibility of evidence may be classified according to the category of cases (civil, labor, family cases, cases of separate proceedings) and the type of evidence (written evidence, material evidence, electronic evidence). Characteristics of the admissibility rule concerning electronic evidence are realized. The author has offered to conduct an expertise for proving the admissibility of electronic documents in a civil case.

Исследована проблематика допустимости доказательств в современном гражданском процессе с учетом обновленной объективной формы существования доказательств и новейших технологий исследования фактических обстоятельств в гражданском деле. Рассмотрены научные дискуссии относительно категории «доказательства» и правовые позиции, сформировавшиеся относительно допустимости доказательств.
Some issues of admissibility of evidence in civil proceedings of Ukraine
Отдельные вопросы допустимости доказательств в гражданском процессе Украины
Keywords: докази; фактичні дані; допустимість доказів; доказування; суд; цивільний процес; proof; evidence; admissibility of evidence; court; civil procedure; доказательства; фактические данные; допустимость доказательств; доказывание; гражданский процесс